(untitled) - Luntz, Perry (Hoboken, N.J., 2007)
Whiskey & Spirits For Dummies is your complete guide to selecting and enjoying this family of noble beverages, flavor by flavor. From whiskey, rum, and brandy to vodka, gin, and cordials, this handy reference traces the history of distilled spirits, explains how they are made, and shows you how to evaluate, serve, and savor them.
Keywords: Whiskey,Alcoholic beverages